Pengaruh Price Earning Ratio (PER), Price Book Value (PBV) dan Debt to Equity Ratio (DER) Terhadap Return Saham (Studi Terhadap Perusahaan Properti dan Real Estate yang Listing di Indeks Saham Syariah Indonesia) - Akbar, Rendra; Herianingrum, Sri (Jurnal Ekonomi Syariah Teori dan Terapan, 2015)
Every investor wants a secure investment and provides profit (in-return). This study aimed to analyze the effect of Price Earnings Ratio (PER), Price Book Value (PBV) and Debt to Equity Ratio (DER) on stock returns Vendor property and real estate listed in Indonesian Sharia Stock Index (ISSI) in the period 2011-2013. This study used quantitative analysis with panel data estimation methods with time series in 2011-2013 and cross section data of thirty-one companies used α = 5% significance level. The regression results in this study indicated that the independent variables Price Earnings Ratio (PER) and variable Debt to Equity Ratio (DER) significantly shown negative effect on stock returns, meanwhile the variable Price Book Value (PBV) significantly shown positive effect on stock returns. While simultaneously brought a significant effect on stock returns and real estate properties listed in Indonesian Sharia Stock Index (ISSI) in period 2011-2013.